Akuntabilitas Dinas Sosial dalam Rehabilitasi Sosial bagi Penyandang Disabilitas di Kota Medan: The Accountability of the Social Service Agency in the Social Rehabilitation for Persons with Disabilities in Medan City - Damayanti, Shinta; Trimurni, Februati (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Social rehabilitation is a process of refunctionalization and development that enables persons with disabilities to perform their social functions appropriately in society through self-adjustment, accessibility services, guidance, and assistance. This study aims to identify and describe the accountability of the Social Service Agency in the social rehabilitation for persons with disabilities in Medan City, using a descriptive research method with a qualitative approach. Data collection was conducted through interviews, observation, documentation, and literature review, with data analysis meliputi data reduction, data presentation, conclusion drawing, and verification. Data validity was ensured using source and technique triangulation. The research findings indicate six obstacles affecting accountability: (1) the absence of Standard Operating Procedures for social rehabilitation services, (2) the slow feedback process regarding public complaints, (3) low public enthusiasm in understanding service mechanisms, (4) the Performance Accountability Report of Government Agencies (LAKIP) not being published openly and periodically, (5) limited human resources and public facilities that are not yet disability-friendly, and (6) the unsuitability of the quality of disability aids and their uneven distribution. All these obstacles have caused the social rehabilitation program to not run effectively, efficiently, and accountably.